Using Social Marketing to Reduce Intention of Cesarean Section in Iranian Women - Mostafa Maleki; Ali Mousavizadeh; Saadat Parhizkar; Mohsen Shams (Journal of Pregnancy)
Introduction. In Iran, the rate of cesarean section is three times more than the acceptable rate considered by the World Health Organization. This study aimed at reducing the selection of cesarean section by primigravida through an intervention based on social marketing in Boyer-Ahmad County, Iran, 2015. Methods. In this field trial, 39 of primigravida women were identified and selected as a target group. Formative research (a quantitative survey and a qualitative study) was done to achieve the social marketing mix. The tailored intervention was developed based on the findings of formative research. The intervention was implemented for one month for pregnant women who had cesarean section intention. Their intention for the cesarean section was studied again one month after the implementation of the intervention. The effectiveness of the intervention was evaluated by the proportion test. Results. The average age of the women was 25.82. All of the women 38.5 percent had a diploma degree and lower than and 61.5 percent had a university degree. Before the intervention, 39 women intended to do Cesarean. The intention of 30 pregnant women was changed significantly one month after the intervention. Conclusion. The study showed the effectiveness of an intervention based on consumer-oriented social marketing theory and could be used to reduce Cesarean intention. More studies about related factors of vaginal delivery selection especially from behavioral intention up to behavior are suggested.